Combined neurosurgical and orbital intervention for spheno-orbital meningiomas - the Manchester experience. (3rd July 2020) - Young, J.; Mdanat, F.; Dharmasena, A.; Cannon, P.; Leatherbarrow, B.; Hammerbeck-Ward, C.; Rutherford, S.; Ataullah, S.
ABSTRACT: Purpose: Surgical resection of spheno-orbital meningioma (SOM) is challenging, requiring a multidisciplinary surgical approach. We present our experience of the surgical management of patients with SOM. Methods: A retrospective analysis of patients with SOM who underwent joint neurosurgical and orbital surgical procedures between January 2000 and June 2017. Pre-operative clinical signs, indication for surgery, surgical complications and post-operative outcomes were recorded. Results: Twenty-four operations were performed. Mean age was 49.5 years. Ninety-two percent of patients were female. Pre-operatively mean Snellen acuity vision was 6/12; 13 (54%) had an RAPD; 12 (50%) had reduced colour vision; 16 (67%) had a visual field defect. The majority (21 patients, 88%) had proptosis (average 4.5 mm ± 2.8 mm). The indication for surgery was evidence of visual dysfunction in 17 (71%), the remaining 7 (29%) had high risk of visual loss clinically or radiologically. Three-months post operatively, vision was stable in 13 (58%), improved in 6 (21%) and worse in 5 (17%). Average long-term follow-up was 82 months (1–220). Fourteen (58%) maintain improved or stable visual function. Four (17%) had reduced vision due to regrowth of the tumour at an average of 24 months. Conclusion: SOMs are very challenging to treat surgically. In this cohort the patients were predominantly young females with aggressive disease. Visual function was improved or stabilised in 79% of the patients.